Enhancing Fine Motor Skills in Children with Cerebral Palsy through Clay-Based Interventions: Implementing a Task Analysis Approach - Al-Mahdi, Ro'id; Rosyidah, Amalia Batul; Shanti, Novita Aria; Maulidina, Putri Fadhilah; Fauzi, Makruf (Universitas Negeri Surabaya, 2025)
Children with cerebral palsy have a main obstacle which is weakness in physical abilities, related to obstacles in muscles and joints either in the hands, feet or other parts of the body. This study aims to explore the effectiveness of clay-based intervention by applying a task analysis approach in improving fine motor skills in cerebral palsy children. Cerebral Palsy (CP) children experience movement disorders caused by impaired brain nerve function, Progressive Dystrophy. Children with disability can be classified into 2 types, namely, orthopedically handicapped children, which is defined as people with disability who experience movement barriers caused by certain deficiencies in muscles, bones, body, and joints. This research is a descriptive quantitative study that uses a Single Subject Research approach. It is a type of research that seeks to change the behavior of individuals or small groups and to document those changes. This research is different from experimental research where the researcher takes a sample and establishes the existence of a control group and behavior group. In Single Subject Research, the subject will serve as both the control group and the behavior group. The research design used in this article is the ABAB research design. ABAB research design is a type of SSR research that involves a baseline phase (A), an intervention phase (B), a second baseline phase (A2), and a second intervention phase (B2). The purpose of using this research design is to demonstrate the functional relationship between the intervention and the subject's behavior. The results showed that clay-based intervention with a task analysis approach was effective in improving fine motor skills in children with cerebral palsy. This study makes an important contribution to the field of special education by offering an innovative and effective intervention approach to improve fine motor skills in children with special needs.